Antimicrobial activity of secondary metabolites produced by Aspergillus neobridgeri isolated from Pistacia lentiscus against multi-drug resistant bacteria - Nouari Sadrati; Amina Zerroug; Rasime Demirel; Sabrina Bakli; Daoud Harzallah (Bangladesh Pharmacological Society, 2020)
The in vitro antibacterial activity of the endophytic fungus Aspergillus neobridgeri PLR9 (isolated from the plant Pistacia lentiscus) against a wide range of tested bacteria were studied. The maximum inhibitory activity was found on malt extract agar medium with a mean inhibitory zone of 11.3 mm (p<0.05). The ethyl acetate extract showed a significant inhibitory zone of 13.4 mm (p<0.05), followed by dichloromethane 9.1 mm. Whereas, n-hexane extract showed no activity. The largest inhibition zones were observed against Staphylococcus aureus 3, S. aureus 5 and Escherichia coli 1 with 21.0 mm of diameter. The MIC's were ranged between 312.5 and 1,250 μg/mL. The MBC's were ≤2500 μg/mL for most Gram positive bacteria and ≥2500 μg/mL for most Gram negative bacteria. Time kill assay study against the Enterococcus faecium showed a bactericidal effect at 4x MIC and bacteriostatic against Acinetobacter baumannii at different concentrations. Moreover, it is the first report, PLR9 isolated as endophyte and studied for their antimicrobial activity.